2021
DOI: 10.3390/en14061608
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mineral Reactive Surface Area on Forecasting Geological Carbon Sequestration in a CO2-EOR Field

Abstract: Mineral reactive surface area (RSA) is one of the key factors that control mineral reactions, as it describes how much mineral is accessible and can participate in reactions. This work aims to evaluate the impact of mineral RSA on numerical simulations for CO2 storage at depleted oil fields. The Farnsworth Unit (FWU) in northern Texas was chosen as a case study. A simplified model was used to screen representative cases from 87 RSA combinations to reduce the computational cost. Three selected cases with low, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 44 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…The initial mineral composition (i.e., primary mineral abundances) of the Morrow B Sandstone was derived from Munson 63 and Gallagher 25 and is shown in Table 3. Also listed are secondary minerals that are expected to have the potential to precipitate due to CO 2 injection, based on previous reaction path and reactive transport modeling studies 37,39,42,48,49,70 . Included in Table 3 are mineral‐specific kinetic reaction data following Kutsienyo et al 42 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial mineral composition (i.e., primary mineral abundances) of the Morrow B Sandstone was derived from Munson 63 and Gallagher 25 and is shown in Table 3. Also listed are secondary minerals that are expected to have the potential to precipitate due to CO 2 injection, based on previous reaction path and reactive transport modeling studies 37,39,42,48,49,70 . Included in Table 3 are mineral‐specific kinetic reaction data following Kutsienyo et al 42 …”
Section: Methodsmentioning
confidence: 99%
“…Also listed are secondary minerals that are expected to have the potential to precipitate due to CO 2 injection, based on previous reaction path and reactive transport modeling studies. 37,39,42,48,49,70 Included in Table 3 are mineral-specific kinetic reaction data following Kutsienyo et al 42 The boundary conditions for the model were governed by the observation that the Morrow B Sandstone reservoir pinches out into adjacent shales…”
Section: Model Setupmentioning
confidence: 99%
“…Wei at al. [17] present a simplified model used to screen representative cases from many mineral reactive surface area (RSA) combinations to reduce computational cost. Three selected cases with low, mid, and high RSA values were used for the FWU model.…”
Section: Riskmentioning
confidence: 99%
“…Carrol et al (2013) identified the critical role of iron-rich clay minerals in a CO 2 storage environment, and the dissolution of iron-rich clay minerals can modify fracture and pore networks by clogging pores via secondary precipitation of Fe carbonates, clays, hydroxides, and amorphous silica [24]. Research found that medium to high reactive surface area minerals in CO 2 -EOR fields reduce the porosity and enhance the CO 2 trapping mechanism [25]. Tutolo et al (2015) found that the precipitation of aluminum-rich secondary minerals in feldspar-rich sandstone can significantly affect the chemical kinetics and reduce permeability [26].…”
Section: Introductionmentioning
confidence: 99%